An endogenous growth model with human and social capital interactions - Sequeira, T. N.; Ferreira-Lopes, A. (Review of Social Economy, 2011)
Social capital has recently been introduced in the economic literature as a source of economic growth. In this paper we study the interactions between social and human capital, and their contributions to economic growth in an endogenous growth model. The model indicates an increase in the relative importance of human capital when compared to social capital throughout the development process of the economy, as also described in some of the empirical literature on the topic. We derive theoretical and policy implications from our endogenous growth model, concluding that a subsidy for human capital has important implications for economic growth and allocation redistribution. A subsidy to social capital is not relevant for economic growth. Its only effect would be the increase in the social to human capital ratio of the economy.